Perancangan Sistem Informasi Pendataan Bantuan Langsung Tunai Di Dinas Sosial Kabupaten Asahan - Fachrul Rozy Arda Rambe; Milfa Aisyaroh; Yahfizham (Journal Of Informatics And Busisnes, 2024)
The design of the Cash Direct Transfer (BLT) Data Collection Information System at the Asahan District Social Office aims to improve efficiency and accuracy in the distribution of social assistance. This system is designed to address the problems of data errors, duplication, and delays in aid delivery. Through a comprehensive approach, from needs analysis to implementation and evaluation, the system integrates the collection, processing, and monitoring of beneficiary data. As a result, this information system is able to support the principles of good governance by increasing transparency and accountability. Training for Social Service officers and the key to successful implementation is to have support from many parties.. This system not only facilitates the management of social assistance in Asahan Regency but also has the capacity to serve as a model for additional locations., thus contributing significantly to improving community welfare and poverty alleviation.